Pasteurization Preserves IL-8 in Human Milk - Giorgi, Marilyn V.; Codipilly, Champa N.; Potak, Debra; Heiman, Howard S.; Schanler, Richard J. (Frontiers in Pediatrics, 2018)
Background: Pasteurized donor human milk is an alternative feeding when mothers' own milk is not available for premature infants. The effects of pasteurization on the host defense properties of human milk are unclear. We investigated the effects of Holder pasteurization on concentrations of anti-inflammatory and pro-inflammatory cytokines in human milk. Objective: To compare concentrations of anti-inflammatory and pro-inflammatory cytokines before and after pasteurization of donor human milk. Study Design: A single milk sample was obtained from each of 24 mothers of premature infants in the neonatal intensive care unit by electric breast pump and was stored at −80°C. At the time of pasteurization, milk samples were thawed and divided into two aliquots. The first aliquot was re-stored at −80°C and the second aliquot was heat-treated at 62.5°C for 30 min and then re-stored at −80°C. At the time of batch cytokine analyses samples were thawed rapidly. Results: Most cytokine concentrations declined following pasteurization. The most prevalent cytokine, IL-8, was preserved (89%) following pasteurization. There were no relationships between gestational age, postnatal age of milk collection, duration of milk storage, and the concentrations cytokines. Conclusion: In contrast to most cytokines after pasteurization, IL-8 is preserved or liberated from another compartment. The maintenance of IL-8 in human milk after pasteurization and the loss of anti-inflammatory cytokines following pasteurization, suggests that the effects of inflammatory activity in pasteurized human milk should be evaluated. These data may account, in part, for the lesser protective effect on the host of pasteurized donor human milk compared with mother's own milk.